Emotions in Public Discourse - Laskowska, Elżbieta (Poznańskie Studia Slawistyczne, 2015)
In political discourse, the recipient is collective and intentional. Being a part of public discourse, political discourse abounds in speech acts that have emotive-evaluative function. In the prezent paper, the Author discusses the most frequent evaluative-emotive acts gleaned from parliamentary speeches, and these include: accusations, complaining, bragging, expressing recognition and justification. The methodological Framework adopted by the Author adheres to the model proposed by Aleksy Awdiejew. Another phenomenon observable in public discourse is aggression. Irrespective of this, expressing emotions in public discourse is sometimes ideologically motivated.